Digitalisasi UMKM dalam Upaya Meningkatkan Penjualan UMKM di Desa Gundi - Lutfiana Maulida; Riska Afifah Rahmawati; Izzah Malikhatus Syarifah; Angga Burhanudin Yahya (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The UMKM digitalization is carried out by utilizing digital technology to expand the marketing of UMKM products through digital marketing. The method used is the observation method by going directly to the UMKM location. The selected UMKMs in this service are UMKM Dua Putra and UMKM Tempe and Soy Milk. After conducting a survey and finding the problems faced by these UMKMs, this service carried out the development of UMKMs by making UMKM product brands and logos, making Google Maps, and making QRIS. The results and benefits obtained from this activity are first, branding UMKM products by giving the name “Tempe Ndeso” and making a logo so that it can increase consumer attractiveness and increase sales. Second, location placement on Google Maps for UMKMs so as to facilitate buyer access and increase visibility. Third, the implementation of the QRIS payment system at the Dua Putra UMKMs for an integrated digital payment system to facilitate transactions and increase payment efficiency.